Covid-19 lockdowns, income distribution, and food security: An analysis for South Africa - Arndt, Channing; Davies, Rob; Gabriel, Sherwin; Harris, Laurence; Makrelov, Konstantin; Robinson, Sherman; Anderson, Lillian (Elsevier, 2020)
Absent vaccines and pharmaceutical interventions, the only tool available to mitigate its demographic effects is some measure of physical distancing, to reduce contagion by breaking social and economic contacts. Policy makers must balance the positive health effects of strong distancing measures, such as lockdowns, against their economic costs, especially the burdens imposed on low income and food insecure households. The distancing measures deployed by South Africa impose large economic costs and have negative implications for the factor distribution of income. Labor with low education levels are much more strongly affected than labor with secondary or tertiary education. As a result, households with low levels of educational attainment and high dependence on labor income would experience an enormous real income shock that would clearly jeopardize the food security of these households. However, in South Africa, total incomes for low income households are significantly insulated by government transfer payments. From public health, income distribution and food security perspectives, the remarkably rapid and severe shocks imposed because of Covid-19 illustrate the value of having in place transfer policies that support vulnerable households in the event of ‘black swan’ type shocks.